(untitled) (Research, Society and Development, 2024)
This study addresses the terminology Obstetric Violence (VO) defined as violence of unnecessary acts or interventions affecting several pregnant women, thus, it is an invasion of the female body by the health professional who neglects women’s rights (Paula et al., 2020). Cesarean section rates show great increase, whose index should be up to 30%, but Brazil is one of the world leaders in this regard. In order to reduce these rates, the Ministry of Health instituted the Humanization Program in Prenatal and Birth, consolidating the humanization technique in childbirth with the purpose of offering access to assistance and quality. The general objective was to identify women who have already suffered Obstetric Violence. The research focused on a microregion, located in the South of Minas Gerais, through the questionnaire applied in Snowball format. For the realization of the project, the municipalities that are part of this microregion with a sample of 38 puerperal women were included. The present study showed that a significant portion of the participants suffered some type of Obstetric Violence and did not seek help due to lack of support, or because they did not know the definition of Obstetric Violence. In addition, according to the questionnaire applied, the lack of ethics in some situations on the part of health professionals was evident. It is of paramount importance that the topic of Obstetric Violence is increasingly discussed, so that there is an awareness in the population so that everyone knows how to act and what measures to take in these situations.